HAK IMUNITAS ADVOKAT DALAM MENJALANKAN PROFESI HUKUM - Andi Nurhidayah (Constitutum: Jurnal Ilmiah Hukum, 2023)
An advocate is someone whose profession is to provide legal services which can be done in court and outside court. As a client's legal representative, an advocate acts as a spokesperson representing the client's interests before court, arbitration, or in negotiations. Advocates compose legal arguments, prepare legal documents, and defend their clients' interests. Advocates' immunity rights are regulated in Article 16 of Law Number 18 of 2003 concerning Advocates which states that advocates cannot be prosecuted, either civilly or criminally, because they carry out their professional duties in good faith for the benefit of client defense. The problem is how to use the right of advocate immunity in resolving criminal cases? And what are the obstacles that arise in using Advocate immunity rights in resolving criminal cases? The method used is a normative legal research method. The use of the right to advocate immunity in resolving criminal cases is a right that is always protected by law, however the granting of this right has limitations, namely moral values, the essence of good faith, honesty, greater legal interests and responsibility. Obstacles to the use of advocates' immunity rights in resolving criminal cases can be seen that there are still a number of advocates who are involved in corruption cases or who obstruct legal officers in uncovering a criminal case.